2002
DOI: 10.1074/jbc.m109412200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Targeting and Clustering Interactions between Heterologously Expressed PSD-95 and the Shal Voltage-gated Potassium Channel, Kv4.2

Abstract: Kv4.2 is a voltage-gated potassium channel that is critical in controlling the excitability of myocytes and neurons. Processes that influence trafficking and surface distribution patterns of Kv4.2 will affect its ability to contribute to cellular functions. The scaffolding/clustering protein PSD-95 regulates trafficking and distribution of several receptors and Shaker family Kv channels. We therefore investigated whether the C-terminal valine-serine-alanine-leucine (VSAL) of Kv4.2 is a novel binding motif for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 56 publications
7
53
0
Order By: Relevance
“…This is demonstrated by the fact that whole-cell Kir2.1 currents recorded in the presence of PSD-93␦ were indistinguishable from those recorded in its absence. Similar results have been obtained for Kv1.4 and Kv4.2 (33,43) and suggest that pathways involved in the insertion or removal of K ϩ channels into or out of the plasma membrane may be more tightly regulated and synchronized than previously thought.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is demonstrated by the fact that whole-cell Kir2.1 currents recorded in the presence of PSD-93␦ were indistinguishable from those recorded in its absence. Similar results have been obtained for Kv1.4 and Kv4.2 (33,43) and suggest that pathways involved in the insertion or removal of K ϩ channels into or out of the plasma membrane may be more tightly regulated and synchronized than previously thought.…”
Section: Discussionsupporting
confidence: 75%
“…A role for MAGUKs in the regulation of channel and receptor surface expression is supported by the finding that deletion of the C-terminal PDZ binding motif of NR2B subunits increases the rate of NMDAR internalization in neurons (34), and by a recent study that shows a reduction of surface NR2A and NR2B expression in spinal dorsal horn neurons of PSD-93 knockout mice (39). The rate of internalization of Kv1.4 and Kv4.2 channels is also reduced when coexpressed with PSD-95 (33,43), and at least in the case of Kv1.4, surface stabilization seems to intimately linked with channel clustering, since PSD-95 mutants that bind but do not cluster Kv1.4 allow rapid channel endocytosis (33). Interestingly, whereas PSD-93␦ suppresses the rate of Kir2.1 internalization, it does not seem to affect the overall level of channel expression at the cell surface.…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, the I2 insert fails to address SAP97 to the membrane, leading to SAP97 accumulation in the cytosol or nucleus (10,29). The subsarcolemmal localization of this SAP97 isoform containing the I2 insert may depend more on protein partners such as protein 4.1 (11) or Kv channels, as described for the membrane redistribution of PSD95 by Kv4.2 Shal channels (30). One consequence of the poor capacity of SAP97 lacking the I3 domain to be correctly addressed to the membrane could be also the formation of aggresomes of misfolded proteins (15,31).…”
Section: Sap97 Isoforms and Hkv15 Shaker Channelsmentioning
confidence: 99%
“…Another synapse-associated protein found to interact with Kv4.2 is the scaffolding protein PSD-95 (216). Using a surface biotinylation assay, Wong et al (216) showed that coexpression of Kv4.2 with PSD-95 in CHO cells enhanced the surface expression of Kv4.2 ϳ2-fold.…”
Section: G Neuron-specific Modulator: Psd-95mentioning
confidence: 99%